Localized Provoked Vulvodynia-An Ignored Vulvar Pain Syndrome - Paavonen, Jorma; Eschenbach, David A. (Frontiers in Cellular and Infection Microbiology, 2021)
Localized provoked vulvodynia (LPV) causes dyspareunia among reproductive aged women. We review the pathogenesis of LPV and suggest that LPV is an inflammatory pain syndrome of the vestibular mucosa triggered by microbial antigens in a susceptible host. Tissue inflammation and hyperinnervation are characteristic findings which explain symptoms and clinical signs. Education of health care providers of LPV is important since this condition is common, often unrecognized, and patients often become frustrated users of health care. Research is needed on the antigen triggers of the syndrome. Randomized clinical trials are needed to evaluate treatment modalities.